2018
DOI: 10.1177/1066896918813678
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of p63/p40 Expression With Myoepithelial Markers in Minor Salivary Gland Tumors

Abstract: The present study aimed to compare the expression of p63/p40 with smooth muscle actin (SMA) and vimentin (VIM) by myoepithelial cells in minor salivary gland tumors. Fifty-two formalin-fixed paraffin-embedded samples of minor salivary gland tumors derived from intercalated duct (pleomorphic adenoma [PA], adenoid cystic carcinoma [ACC], epithelialmyoepithelial carcinoma [EMC], polymorphous adenocarcinoma [PAC], and secretory carcinoma [SC]) and 3 samples of minor salivary gland tumors derived from excretory duc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Compared with the low specificity of radiologic imaging, immunohistochemistry is useful for distinguishing EMCa, as it can depict the characteristic biphasic epithelialmyoepithelial phenotype and the differential staining of markers in each layer; thus, it plays a major role in the final diagnosis (2,10). IHC staining of glandular epithelial markers such as CK, epithelial membrane antigen (EMA), and CD117 (11) and myoepithelial markers such as SMA, S-100 protein, Actin, VIM, CK14, GFAP and Calponin, and P63 is observed (45)(46)(47). Kawahara et al suggested that P63 is an especially useful marker of myoepithelial cells with naked nuclei in EMCa (48).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the low specificity of radiologic imaging, immunohistochemistry is useful for distinguishing EMCa, as it can depict the characteristic biphasic epithelialmyoepithelial phenotype and the differential staining of markers in each layer; thus, it plays a major role in the final diagnosis (2,10). IHC staining of glandular epithelial markers such as CK, epithelial membrane antigen (EMA), and CD117 (11) and myoepithelial markers such as SMA, S-100 protein, Actin, VIM, CK14, GFAP and Calponin, and P63 is observed (45)(46)(47). Kawahara et al suggested that P63 is an especially useful marker of myoepithelial cells with naked nuclei in EMCa (48).…”
Section: Discussionmentioning
confidence: 99%
“…The different immunophenotype of the abluminal cells may simply represent two different differentiations from ductal progenitor cells. Moreover, although SMA is a sensitive marker for myoepithelial differentiation it should not be the sole myoepithelial marker, because any cell with substantial expression of actin can be positive for SMA due to its low specificity 15 . To date, only one case has shown SMA staining in abluminal cells, and further research is necessary to characterise these cells in pulmonary SP.…”
Section: Immunohistochemical Featuresmentioning
confidence: 99%
“…Moreover, although SMA is a sensitive marker for myoepithelial differentiation it should not be the sole myoepithelial marker, because any cell with substantial expression of actin can be positive for SMA due to its low specificity. 15 To date, only one case has shown SMA staining in abluminal cells, and further research is necessary to characterise these cells in pulmonary SP. SOX10 was strongly expressed in both luminal and basal cells in all five cases with staining (100%) (Figure 2D).…”
Section: Immunohistochemical Featuresmentioning
confidence: 99%